2020
DOI: 10.2196/17134
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Fairness of Privacy Policies of Mobile Health Apps: Scale Development and Evaluation in Cancer Apps

Abstract: Background Cancer patients are increasingly using mobile health (mHealth) apps to take control of their health. Many studies have explored their efficiency, content, usability, and adherence; however, these apps have created a new set of privacy challenges, as they store personal and sensitive data. Objective The purpose of this study was to refine and evaluate a scale based on the General Data Protection Regulation and assess the fairness of privacy po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 52 publications
(78 reference statements)
4
34
0
Order By: Relevance
“…According to the results, most of the apps collected in the initial sample (33/45, 73%) included a privacy policy, which was similar to a previous assessment of cancer apps by Benjumea et al [ 22 ] who found that 71% of the apps in their sample had a privacy policy. Considering that the prevalence of privacy policies for high-download apps is significantly higher than that of low-download apps (high downloads: 15/17, 88%; and low downloads: 33/64, 52%; P =.006) [ 31 ], our result might be higher than the actual situation.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…According to the results, most of the apps collected in the initial sample (33/45, 73%) included a privacy policy, which was similar to a previous assessment of cancer apps by Benjumea et al [ 22 ] who found that 71% of the apps in their sample had a privacy policy. Considering that the prevalence of privacy policies for high-download apps is significantly higher than that of low-download apps (high downloads: 15/17, 88%; and low downloads: 33/64, 52%; P =.006) [ 31 ], our result might be higher than the actual situation.…”
Section: Discussionsupporting
confidence: 82%
“…The level 3 indicators under policy disclosure and policy updates can maintain a scoring rate of 57%-58%, which indicated that most PI controllers had a basic awareness of protecting user privacy. However, only 48% (16/33) of apps introduce the basic information of the PI controller in the privacy policies, which is far lower than a previous study (77%) [ 22 ].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…To perform a more complete assessment of apps’ privacy risks, additional technical, human, and contextual research (eg, analysis of the skills of patients using diabetes apps) should be conducted. For example, when dealing with privacy issues in health apps, an important factor to be considered would be the legitimacy of the request, as highlighted in a recent publication on mHealth apps for cancer in which the authors evaluated a new scale to assess the privacy policies of mHealth apps [ 51 ]. Tracking users’ location might be fair in the case of reporting a medical emergency (eg, hypoglycemic crisis).…”
Section: Discussionmentioning
confidence: 99%